An alternative theory of real exchange rate determination: theory and empirical evidence for the Mexican economy, 1970-2004 - Martínez Hernández, Francisco A. (Investigación Económica, 2011)
The recent history of the Mexican economy has shown that its worst economic crises have been due to balance of payments problems, which eventually lead to foreign exchange rate crises (1976-1977, 1982, 1986-1988 and, 1994-1995). Although conventional exchange rate models hold that in the long-run real exchange rates will move in such a way as to make countries equally competitive, such an argument is far from being true because in reality countries are unequally competitive. In the case of Mexico (Mex), a clear and thorough assessment of real exchange rate determination and its relationship with the balance of payment, especially with the current account, which has been negative since the late forties despite currency devaluations, is necessary.